Epilepsy-causing Reelin mutations result in impaired secretion and intracellular degradation of mutant proteins. Issue 5 (11th September 2021) - Dazzo, Emanuela; Nobile, Carlo
Abstract: Autosomal dominant lateral temporal epilepsy (ADLTE) is a genetically heterogeneous neurologic disorder clinically characterized by focal seizures with auditory symptoms and/or aphasia. About 20% of ADLTE families segregate disease-causing heterozygous mutations in RELN, a brain-expressed gene encoding the secreted protein Reelin. Using a cell-based secretion assay, we show that pathogenic RELN mutations abolish or significantly reduce secretion of mutant proteins and that this secretion defect results from impaired trafficking of mutant Reelin along the secretory pathway. Confocal immunofluorescence analysis of transiently transfected cells shows that Reelin mutant proteins are degraded by the autophagy system, as revealed by increased formation of autophagosomes immunoreacting with the autophagy markers p62 and LC3. In addition, LC3 immunoblotting shows a significant increase of autophagy flux due to mutant overexpression. Finally, we show that the secretion defect of mutant proteins can be partially rescued by small-molecule correctors. Altogether, these results suggest that Reelin mutant proteins are not properly secreted and that they are degraded through the autophagy pathway.